2014
DOI: 10.1371/journal.pone.0085720
|View full text |Cite
|
Sign up to set email alerts
|

Proper PIN1 Distribution Is Needed for Root Negative Phototropism in Arabidopsis

Abstract: Plants can be adapted to the changing environments through tropic responses, such as light and gravity. One of them is root negative phototropism, which is needed for root growth and nutrient absorption. Here, we show that the auxin efflux carrier PIN-FORMED (PIN) 1 is involved in asymmetric auxin distribution and root negative phototropism. In darkness, PIN1 is internalized and localized to intracellular compartments; upon blue light illumination, PIN1 relocalize to basal plasma membrane in root stele cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 48 publications
(88 reference statements)
1
20
0
Order By: Relevance
“…In this work, we show that differential flavonol accumulation in the organ sides regulates root negative phototropism. Physiological studies have shown that negative root phototropism is regulated by an asymmetrical auxin redistribution (Wan et al, 2012;Zhang et al, 2013Zhang et al, , 2014. Connected with this regulation, quercetin and kaempferol, the two main Arabidopsis flavonols (Winkel-Shirley, 2002), inhibit auxin transport Peer et al, 2004).…”
Section: Discussion Flavonols Mediate Root Phototropic Responsesmentioning
confidence: 99%
See 2 more Smart Citations
“…In this work, we show that differential flavonol accumulation in the organ sides regulates root negative phototropism. Physiological studies have shown that negative root phototropism is regulated by an asymmetrical auxin redistribution (Wan et al, 2012;Zhang et al, 2013Zhang et al, , 2014. Connected with this regulation, quercetin and kaempferol, the two main Arabidopsis flavonols (Winkel-Shirley, 2002), inhibit auxin transport Peer et al, 2004).…”
Section: Discussion Flavonols Mediate Root Phototropic Responsesmentioning
confidence: 99%
“…Tropic responses, which involve organ curvature, occur due to asymmetric growth between sides of the root and normally correlate with an asymmetric distribution of the plant hormone auxin (Mähönen et al, 2014;Wang et al, 2015). Reorientation of root growth during the light avoidance response might require a local response in the transition zone mediated by PHOT1 (Zhang et al, 2014). The role of auxin in phototropism has also been studied (Esmon et al, 2006;Stone et al, 2008;Haga and Sakai, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Downstream of directional light perception, polar auxin transport directs auxin away from the illuminated side. This auxin transport gradient requires rootward plasma membrane localization of the auxin efflux carrier PIN1 in the stele, lateral relocalization of PIN3 in the columella, and rootward relocalization of PIN2 in the epidermis (Wan et al, 2012;Zhang et al, 2013Zhang et al, , 2014. The relocalization of PIN2 and PIN3 is dependent upon the recycling and targeted degradation (vacuolar targeting) of these PIN carriers from one side of the membrane to the other (Wan et al, 2012;Zhang et al, 2013).…”
Section: Root Negative Phototropismmentioning
confidence: 99%
“…Light influences the direction of polar auxin transport by controlling the plasma membrane abundance of PIN proteins (Laxmi et al, 2008;Sassi et al, 2012;Wan et al, 2012;Zhang et al, 2013Zhang et al, , 2014). An interesting example of how light interacts with the gravitropic output is the U-turn that an inverted maize (Zea mays) seedling root makes when growing in a glass tube exposed to light (Burbach et al, 2012;Suzuki et al, 2016).…”
Section: Interaction Of Light and Gravitropismmentioning
confidence: 99%